F Forest and Negative Peace; An Effect to the Global Peace - Yunita Asmawati (Global Political Studies Journal, 2019)
Forest and Negative Peace; An Effect to the Global Peace The presence of global peace likewise the conflict could be triggered by the environment such as forest degradation of some states. As presently, climate change has been occurred all over the globe and causes conflict. However, this study used the Galtung thought of peace to discover the peace side through qualitative methodology with all the complexity. Therefore, it revealed some classifications of peace notably each characteristic of the peace as far as the metapsychology of peace. Furthermore, it showed how the environment naturally can lead to global peace.